2020
DOI: 10.1111/ctr.14038
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating patient and caregiver feedback into lung transplant referral guidelines for individuals with cystic fibrosis—Preliminary findings from a novel paradigm

Abstract: Background Lung transplantation is a common therapeutic option for individuals with cystic fibrosis (CF) and advanced lung disease, yet many individuals with CF are not appropriately referred for evaluation. The present study sought to enhance CF transplant referral guidelines by integrating patient‐centered input to identify possible psychosocial barriers contributing to suboptimal referral for appropriate CF transplant candidates. Methods As a component of developing the Cystic Fibrosis Foundation (CFF) Lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…All participants felt that the information they received was appropriate for them. In contrast, a recent study of patients with cystic fibrosis undergoing transplantation identified the need to offer more detailed information to broaden their understanding of the situation, and also the need for greater coordination in treatment transition issues, earlier introduction of the transplant option, and broader social support (Smith et al, 2020 ). These differences are likely to be related to the point in the care process at which the study is carried out, since the perception of our participants may differ pre‐ and post‐transplant.…”
Section: Discussionmentioning
confidence: 99%
“…All participants felt that the information they received was appropriate for them. In contrast, a recent study of patients with cystic fibrosis undergoing transplantation identified the need to offer more detailed information to broaden their understanding of the situation, and also the need for greater coordination in treatment transition issues, earlier introduction of the transplant option, and broader social support (Smith et al, 2020 ). These differences are likely to be related to the point in the care process at which the study is carried out, since the perception of our participants may differ pre‐ and post‐transplant.…”
Section: Discussionmentioning
confidence: 99%
“…30 Conversely, encouraging research is emerging regarding the significant and positive impact of CFTR modulators elexacaftor/tezacaftor/ ivacaftor and ivacaftor (Trikafta and Kalydeco, Vertex Pharmaceuticals Incorporated) on many facets of self, including self-image, selfconfidence, autonomy, and physical self-esteem. 31,32 Interestingly however one study reports expression of concerns regarding drug dependency and body representation changes in a small number of participants. 32 Future CF self-concept research needs to factor in the era of CFTR modulator care to ensure self-concept understanding F I G U R E 2 Self-concept dimensions.…”
Section: Self-concept and Health-related Outcomesmentioning
confidence: 99%
“…Not specified Lung transplanted Smith et al 31 Clinical strategies to enhance self-efficacy surrounding lung transplantation process: 1. Early transplant conversations when patients are healthier may decrease anticipatory fear and facilitate proactive engagement with transplant providers once appropriate.…”
Section: Clinical Recommendations Sample and Authorsmentioning
confidence: 99%
See 2 more Smart Citations